2018
DOI: 10.1038/s41598-018-26753-2
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk among lncRNAs, microRNAs and mRNAs in the muscle ‘degradome’ of rainbow trout

Abstract: In fish, protein-coding and noncoding genes involved in muscle atrophy are not fully characterized. In this study, we characterized coding and noncoding genes involved in gonadogenesis-associated muscle atrophy, and investigated the potential functional interplay between these genes. Using RNA-Seq, we compared expression pattern of mRNAs, long noncoding RNAs (lncRNAs) and microRNAs of atrophying skeletal muscle from gravid females and control skeletal muscle from age-matched sterile individuals. A total of 852… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 56 publications
3
48
1
Order By: Relevance
“…In mammals, the intramuscular fat content exhibits a significant negative correlation with moisture content [23,24]. In fish, this correlation depends greatly on the energetic demands associated with various physiological conditions [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the intramuscular fat content exhibits a significant negative correlation with moisture content [23,24]. In fish, this correlation depends greatly on the energetic demands associated with various physiological conditions [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are negative regulators of gene expression via decreasing the stability of target RNAs or limiting their translation. Recently, evidence has shown that lncRNAs and mRNAs can bind a miRNA binding site and that miRNA acts as a sponge [29,50]. In the present study, we constructed lncRNA-miRNA-mRNA networks for sex-speci c expression based on high-throughput sequencing data in the turtle.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are negative regulators of gene expression, decreasing the stability of target RNAs or limiting their translation. Recently, evidence has shown that lncRNA and mRNA could bind the miRNA binding site, and that miRNA acts as a sponge [29,50]. In the present study, we constructed lncRNA-miRNA-mRNA networks for sex different expression based on the high-throughput sequencing data in the turtle.…”
Section: Construction Of Cerna Networkmentioning
confidence: 98%